2018
DOI: 10.1111/jgh.14539
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori and low‐dose aspirin ulcer risk: A meta‐analysis

Abstract: Background and Aim Owing to wide‐spread use, low‐dose aspirin (LDA) produces a substantial amount of peptic ulcer disease. Current guidelines are ambivalent about the need for Helicobacter pylori eradication to protect against LDA ulcers. This study aimed to determine, through meta‐analysis, if (and by how much) infection alters the baseline risk of peptic ulcers during LDA therapy. Methods Literature screening was performed in MEDLINE and EMBASE from inception to May 2018. Original studies reporting prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 34 publications
0
14
0
1
Order By: Relevance
“…Furthermore, even in this consensus, there were no specific advices regarding non-aspirin antiplatelet agents or oral anticoagulants [86]. After these guidelines have been issued, two meta-analyses were published [87,88]. The former showed that H. pylori infection increased the risk of gastroduodenal ulcers during LDA therapy by approximately 70% (OR: 1.65; 95% CI: 1.29-2.08) [87].…”
Section: H Pylori Infection and Risk Of Peptic Ulcer Bleeding In Patmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, even in this consensus, there were no specific advices regarding non-aspirin antiplatelet agents or oral anticoagulants [86]. After these guidelines have been issued, two meta-analyses were published [87,88]. The former showed that H. pylori infection increased the risk of gastroduodenal ulcers during LDA therapy by approximately 70% (OR: 1.65; 95% CI: 1.29-2.08) [87].…”
Section: H Pylori Infection and Risk Of Peptic Ulcer Bleeding In Patmentioning
confidence: 99%
“…After these guidelines have been issued, two meta-analyses were published [87,88]. The former showed that H. pylori infection increased the risk of gastroduodenal ulcers during LDA therapy by approximately 70% (OR: 1.65; 95% CI: 1.29-2.08) [87]. The latter found that the odds of UGIB in patients taking LDA was almost two-and-one-half times as frequent in H. pylori-positive (OR: 2.32; 95% CI: 1.25 -4.33) [88].…”
Section: H Pylori Infection and Risk Of Peptic Ulcer Bleeding In Patmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarri et al performed a meta‐analysis aimed at risk assessment of PUD in low‐dose aspirin users with H pylori infection. The authors included 10 cross‐sectional studies and 7 randomized trials . H pylori infection increased the risk of PUD in case of low‐dose aspirin intake, by 70% in subjects taking acid‐suppressive drugs, and doubled the risk in people without antisecretory drugs.…”
Section: Gastric Diseasesmentioning
confidence: 99%
“…Recently, new guidelines for cardiovascular diseases have been published, and extensive use of both antithrombotic and anticoagulant therapy is recommended [8]. In previous studies, it has been documented that NSAIDs result in a fourfold increased risk of bleeding from a peptic ulceration, while ASA and the presence of H. pylori double the risk [9]. With concurrent use of NSAIDs and H. pylori infection, there is an eightfold increased risk of ulcer bleeding [2].…”
Section: Introductionmentioning
confidence: 99%